Recurrence and resistance risk factors in low-risk gestational trophoblastic neoplasia - Branco-Silva, Mariza [UNESP]; Maestá, Izildinha [UNESP]; Horowitz, Neil; Elias, Kevin; Seckl, Michael; Berkowitz, Ross (Elsevier, 2024)
Gestational trophoblastic neoplasia (GTN) is a group of rare but highly curable pregnancy‐related tumors, especially in low-risk cases. However, around 25% of patients with GTN develop either resistant or recurrent disease after initial chemotherapy. To enhance the understanding of the mechanisms driving treatment failures and to develop more personalized and effective therapeutic strategies, this review explored diverse factors influencing low-risk GTN prognosis. These factors include FIGO (International Federation of Gynecology and Obstetrics) risk score, histology, patient age, pregnancy type, human chorionic gonadotropin (hCG) levels, disease duration, tumor characteristics, metastasis, Doppler ultrasonography, and consolidation chemotherapy. Additionally, the review examined independent risk determinants for disease recurrence and resistance to single-agent chemotherapy in patients with low-risk GTN. In most previous studies on the risk factors related to low-risk GTN, resistance and recurrence have typically been examined independently, despite their overlapping and interrelated nature. Furthermore, they often involve small sample sizes, suffer from methodological shortcomings, and exhibit limited statistical power. Studies utilizing multivariate analysis have shown that independent risk determinants for resistance to first-line treatment include FIGO score, metastatic disease, pre-treatment hCG level, interval between antecedent pregnancy and GTN diagnosis, tumor size, uterine artery pulsatility index (UAPI), choriocarcinoma, lung metastases, lung nodule size, and clearance hCG quartile. The independent predictive factors associated with recurrence include lung metastases, lung nodule size, interval between antecedent pregnancy and chemotherapy, interval from first chemotherapy to hCG normalization, post-delivery low-risk GTN, number of chemotherapy courses to achieve hCG normalization, and number of consolidation chemotherapy cycles. However, while these identified predictive factors offer valuable guidance, the variability in definitions and populations across studies may have implications for the generalizability of their findings. A comprehensive approach using clear definitions and taking into account multiple predictive factors may be necessary for accurately assessing the risk of resistance and recurrence in patients with low-risk GTN.